Lessons shared and engagements made with private and public investors - Dawes, Michael; Mushongachiware, Rodney (CGIAR, 2024)
This report provides an update on work that started in 2022 on two inclusive business models supporting agroecological transitioning in Zimbabwe. Agrowth is contracting smallholder sorghum farmers in Mbire district whilst Hamara have introduced the improved Sasso chicken breed to communities in Murehwa. The 2023/24 season was characterised by the worst drought in living memory for most. Despite this, both companies are eager to press on because the business cases are still valid, for farmers and companies alike. Both company models were found to be supporting agroecological transitioning in their respective districts. They are aligned to principles such as recycling, input reduction, soil and animal health, synergies, economic diversification, co-creation of knowledge, social values and diets, fairness and connectivity. Access to finance by farmers is problematic – there are few options other than the sale of crops and livestock. In Murehwa savings clubs are vibrant and support poultry production, unlike in Mbire where farmers tend to spend their money on household needs. There are opportunities to use this model to further support production in both areas. Government’s presidential input support programme is also an important safety net for farmers. Continued investment by AE-I will be important, not only because of the past drought, but because farmers and companies alike are upbeat about the interventions, and willing to continue investing in the models. The 2024/25 season is predicted to have above average rainfall, and increased productivity will set the two models on the road to sustainability.